Genetic and morphological characterisation of a new species of the genus Hysterothylacium (Nematoda) from Paralichthys isosceles Jordan, 1890 (Pisces: Teleostei) of the Neotropical Region, state of Rio de Janeiro, Brazil - Marcelo Knoff; Nilza Nunes Felizardo; Alena Mayo Iñiguez; Arnaldo Maldonado Jr; Eduardo José L Torres; Roberto Magalhães Pinto; Delir Corrêa Gomes (Memorias do Instituto Oswaldo Cruz, 2012)
Taking into account the difficulties of taxonomic identification of larval anisakid nematodes based on morphological characters, genetic analyses were performed, together with those usually applied, in order to identify anisakid larvae found in the flounder Paralichthys isosceles from the littoral of the state of Rio de Janeiro, Brazil. The analysis of 1,820 larvae revealed a new species, similar to Hysterothylacium MD, Hysterothylacium 2, Hysterothylacium KB and Hysterothylacium sp regarding the absence of the larval tooth, an excretory pore situated below the nerve ring level, and slender lateral alae. Moreover, the new species differs from Hysterothylacium fortalezae and Hysterothylacium reliquens with regard to the number and size of spines present on the tail end and from Hysterothylacium patagonicus by the absence of interlabia. The maximum parsimony and neighbour joining tree topologies based on the 18S ribosomal DNA gene, complete internal transcribed spacer region and cytochrome oxidase 2 (COII) gene demonstrated that the Brazilian larvae belong to Raphidascarididae and represent a unique genetic entity, confirmed as a new Hysterothylacium species. Furthermore, the new species presents COII genetic signatures and shares polymorphisms with Raphidascarididae members. This is the first description of a new anisakid species from Brazil through the integration of morphological and molecular taxonomy data.